Characteristics of historical precipitation for winter wheat cropping in the semi-arid and semi-humid area - Fang, Dan; Huang, Jingyao; Sun, Weiwei; Ullah, Najeeb; Jin, Suwen; Song, Youhong (Frontiers in Plant Science, 2023)
Winter wheat is one of major crops in the area along Huai river, China where it is a semi-arid and semi-humid region with sufficient precipitation for an entire season, but with uneven distribution within various growth stages. Effect of waterlogging and drought on wheat grain yield is highly development stage specific. Therefore, it is essential to characterise the precipitation associated with different crop developmental stages. Based on climate data from 1999 to 2020 in six representative meteorological stations, we characterised the historical precipitation relating to seven key growth stages in winter wheat. There is no clear trend of interannual variation of precipitation for wheat season, with an average of precipitation of 414.4±121.2 mm. The precipitation amount was relatively higher in overwintering or maturation stage and lower in sowing or booting stage. In terms of the distribution of precipitation grade within a season, light rain was dominant during the pre-winter seedling and over-wintering stages, while torrential rain only occurred during the heading-filling and maturation stages. Continuous rain occurred frequently during the pre-winter seedling and overwintering stages and more often lasted the longest during the sowing stage. In conclusion, these findings provide a foundation for instructing winter wheat cropping in confronting with waterlogging and drought risk due to uneven precipitation in ‘Yanhuai’ region, China.